Gereja dan Alkitab: Sebuah Perjalanan Sejarah yang Membangun Iman dan Praktik Spiritual di Tengah Umat Kristiani - Surudiaman Lase; Malik Bambangan (Anugerah : Jurnal Pendidikan Kristiani dan Kateketik Katolik, 2025)
This article looks at how the church and the Bible have developed in the past as important factors influencing Christian communities' faith and spiritual practices. Since its beginning, the church has been the main institution for spreading the teachings of Christ, and the Bible has served as the foundational source of spiritual authority. The church has also grown from the early days of Christianity to the Reformation and up to today. Through a historical-theological approach, this article aims to provide a deeper understanding of the role of the church and the Bible in building faith and strengthening the spiritual practices of Christians. Through a historical-theological approach, this article aims to provide a deeper understanding of the role of the church and the Bible in building faith and strengthening the spiritual practices of Christians.